Knowledge Level and Adoption Behaviour of Maize Growers in Selected Districts of Nagaland, India - Patra, Nirmal Kr; Chophi, Vitoka; Sanjoy Das, (Indian Journal of Extension Education, 2023)
The paper examined the knowledge level and adoption behaviour of maize growers in Nagaland. Altogether, 120 respondents were selected following proportionate random sampling from 8 villages from four blocks of two districts. Two indices, namely, knowledge and adoption indices were developed. The maize growers had inadequate knowledge of improved cultivation practices of maize. Respondents had inadequate adoption index. The variables- age, marital status, and family size had having statistically significant relationship at 5% with knowledge level. Simultaneously, income from maize cultivation, informal information, mass media, social participation, and experience in maize cultivation established a statistically significant relationship at 1% with the knowledge level. Similarly, marital status, education, and informal sources of information established a statistically significant relationship at 5% with the adoption level, and annual income was found to be statistically significant at 1% with the adoption level. It is recommended that all the stakeholders and extension systems take the initiative to improve maize cultivation in Nagaland, which will accelerate the socio-economic up-scaling of the study community. Concerned authorities may also carry out frequent capacity development and technology transfer drives for improvement.